2020
DOI: 10.1002/hep.31309
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hepatocellular Carcinoma Surveillance in Patients With Cirrhosis: A Systematic Review and Meta‐Analysis

Abstract: Background and Aims Hepatocellular carcinoma (HCC) surveillance is associated with early tumor detection and improved survival; however, it is often underused in clinical practice. We aimed to characterize surveillance use among patients with cirrhosis and the efficacy of interventions to increase surveillance. Approach and Results We performed a systematic literature review using the MEDLINE database from January 2010 through August 2018 to identify cohort studies evaluating HCC surveillance receipt or interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
162
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 204 publications
(173 citation statements)
references
References 55 publications
(93 reference statements)
9
162
2
Order By: Relevance
“…Albumin, g/dL 3.4 (2.9-3.8) 3.5 (3.4 -3. ll will enable individual risk-based personalized HCC screening by guiding the allocation of the limited medical resources for the semi-annual HCC screening (resources that accommodate only <25% of the guideline-recommended target patient population for the HCC screening 5 ) to a subset of patients with elevated HCC risk. Moreover, the PLSec-based high-risk patients will be the rational target for HCC screening with new high-performance modalities (e.g., circulating cell-free methylated DNA associated with HCC occurrence within 8 months 28 ) to improve early tumor detection and prolong patient survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Albumin, g/dL 3.4 (2.9-3.8) 3.5 (3.4 -3. ll will enable individual risk-based personalized HCC screening by guiding the allocation of the limited medical resources for the semi-annual HCC screening (resources that accommodate only <25% of the guideline-recommended target patient population for the HCC screening 5 ) to a subset of patients with elevated HCC risk. Moreover, the PLSec-based high-risk patients will be the rational target for HCC screening with new high-performance modalities (e.g., circulating cell-free methylated DNA associated with HCC occurrence within 8 months 28 ) to improve early tumor detection and prolong patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, with this ''one-size-fits-all'' strategy, the large at-risk patient population overburdens limited medical resources, as evidenced by the low utilization of HCC screening (<25%). 5 As a consequence, the majority of HCCs are diagnosed at late stages and not amenable to curative treatment, which accounts for its overall poor prognosis (5-year survival <15%). Thus, the precise prediction of future HCC risk could enable more effective HCC screening by identifying a subset of cirrhosis patients at higher HCC risk and allocating limited resources to high-risk patients.…”
Section: Introductionmentioning
confidence: 99%
“…The first large studies to demonstrate underuse of surveillance were large population-based studies from the Surveillance Epidemiology and End Results-Medicare and national VA databases, with both studies showing less than 20% of patients had received an ultrasound or AFP in 2 of the 3 years prior to HCC diagnosis [ 23 , 24 ]. Since that time, several cohort studies have similarly shown HCC surveillance is underused, with a recent meta-analysis finding a pooled surveillance utilization of 24.0% (95% CI: 18.4–30.1%) [ 25 ]. In subgroup analyses, the highest surveillance receipt was reported in studies including patients from subspecialty gastroenterology clinics and the lowest surveillance receipt in studies using population-based cohorts (73.7 vs 8.8%).…”
Section: Effectiveness Of Hcc Surveillancementioning
confidence: 99%
“…Although this availability provides a foundation for HCC surveillance programs, data from the Western world have highlighted that this is essential but not sufficient, with continued underuse of surveillance in clinical practice. 2 In addition to providers reporting competing clinical concerns, patient-reported barriers such as transportation and costs are associated with lower surveillance receipt. 3 These patient-and provider-level barriers may be even more prevalent in resource-limited countries and would need to be aggressively addressed.…”
Section: To the Editormentioning
confidence: 99%
“…Interventions such as reminder systems for providers and population health strategies for patients can significantly increase HCC surveillance receipt but have not been evaluated in routine clinical practice or resource-limited settings. 2 Although advances in surveillance biomarkers offer promise for improved effectiveness of early detection efforts, studies will be needed to assess their effectiveness in areas such as sub-Saharan Africa as only 2 of the 5 centers had consistent access to AFP testing.…”
Section: To the Editormentioning
confidence: 99%